1983
DOI: 10.1007/bf00155936
|View full text |Cite
|
Sign up to set email alerts
|

Integration of pines, pastures, and cattle in south Georgia, USA

Abstract: Native forages of the southern United States are frequently low in nutrients and poorly digestible, while improved pastures are the opposite. Since this area produces rapid growth of pines, which is a major use of the land, the integration of pines, pastures, and cattle seem to offer an efficient and economical form of management. Therefore, in a 20-year study Coastal bermuda (Cynodon dactylon), dallis (Paspalum dilatatum), and Pensacola bahia (P. notatum) grasses were grown in pastures with no trees, and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
14

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 11 publications
3
29
0
14
Order By: Relevance
“…There were only small differences in gains as influenced by tree spacings because both spacings had the same density. These animal responses are similar to those at similar plantation ages from the earlier study of combining pines and pastures [13].…”
Section: Cattle Responsessupporting
confidence: 79%
See 2 more Smart Citations
“…There were only small differences in gains as influenced by tree spacings because both spacings had the same density. These animal responses are similar to those at similar plantation ages from the earlier study of combining pines and pastures [13].…”
Section: Cattle Responsessupporting
confidence: 79%
“…The proven shade tolerance of Pensacola bahiagrass over Coastal bermudagrass [6,13] could become very important when pine crowns provide more a None of the differnces were statistically significant at the 0.05 level Figure 3. Beef production from pastures planted with widely-spaced rows of pines was high since shading had a minimum influence on the grasses.…”
Section: Cattle Responsesmentioning
confidence: 93%
See 1 more Smart Citation
“…The response with AVGLAI demonstrated that CP of SB leaves at LAI levels below 0.5 almost reached 80 g kg -1 , but CP remained above 250 g kg -1 when the overstory LAI was greater than 3.0. The response of leaf CP to light levels corresponds with other studies (Allard et al 1991;Kephart and Buxton 1993;Lewis et al 1983). Although shading appears to have a positive influence on tissue CP content, shading is commonly reported to lower soluble carbohydrate level in plants contributing to a decline in herbage dry matter digestibility (Wilson 1984;Buxton and Casler 1993).…”
Section: Grass and Bft Cpsupporting
confidence: 85%
“…Several studies conducted since then have produced results influencing the practice of silvopasture (Halls et al, 1957;Lewis et al, 1983;Lewis & Pearson, 1987;Pearson & Rollins, 1987;Clason, 1995;Zinkhan & Mercer, 1997), especially in the configuration of trees and the type of forage grass used by landowners. Recent work in silvopastoral systems suggests that compared with treeless pastures, silvopasture might have a greater potential to sequester carbon (C) (Haile et al, 2006), and also to remove excess nutrients (Nair et al, 2007) particularly from the deeper horizons of sandy soils which could result in environmental improvement of agricultural lands.…”
Section: Introductionmentioning
confidence: 99%